Maternal exposure to arsenic in drinking water and risk of congenital heart disease in the offspring. (February 2022) - Richter, Frida; Kloster, Stine; Wodschow, Kirstine; Hansen, Birgitte; Schullehner, Jörg; Kristiansen, Søren Munch; Petersen, Mette Mains; Strandberg-Larsen, Katrine; Ersbøll, Annette Kjær
Graphical abstract: Highlights: Maternal exposure to arsenic is suspected to impair fetal health. A dose-response association between maternal arsenic exposure and CHD was found. Arsenic levels as low as 0.5–0.9 μg/L increased the risk of CHD. Sex did not modify the association. Abstract: Introduction: Prenatal exposure to arsenic is suspected to impair fetal health, including congenital malformations. Few studies investigated an association between maternal exposure to arsenic and congenital heart disease. Objective: To examine the association between maternal exposure to arsenic through drinking water and congenital heart disease among offspring. Methods: This nationwide cohort study included all liveborn children in Denmark, 1997–2014. Maternal addresses at fetal age 4 weeks were linked to drinking water supply areas. Exposure was arsenic concentration in drinking water in first trimester in four categories (<0.5 μg/L, 0.5–0.9 μg/L, 1.0–4.9 μg/L, ≥5.0 μg/L). Outcomes were defined as congenital heart disease diagnosed within the first year of life, with sub-categorization of severe, septal defects and valvular heart defect. Associations between arsenic levels and congenital heart disease were analysed using logistic regression, presented as odds ratios (OR) with 95% confidence interval (CI), and adjusted for year of birth, mother's educational level and ethnicity. Results: A total of 1, 042, 413 liveborn children were included of whom 1.0% had a congenital heart disease. The OR of congenital heart disease was higher among children exposed to all levels of arsenic above 0.5 μg/L; the OR was 1.13 (95% CI: 1.08–1.19) for exposure of 0.5–0.9 μg/L, 1.33 (95% CI: 1.27–1.39) for 1.0–4.9 μg/L and 1.42 (95% CI: 1.24–1.63) for ≥5.0 μg/L. Similar associations were observed for congenital septal defects. The OR was also higher for severe congenital heart disease but at the same level among all exposure levels ≥0.5 μg/L. The OR of congenital valvular heart defects was only higher among children with maternal exposure to arsenic in drinking water ≥5.0 μg/L. The associations were similar for boys and girls. Conclusion: The findings indicate that maternal exposure to arsenic in drinking water even at low concentrations (i.e., 0.5–0.9 μg/L) increased the risk of congenital heart disease in the offspring.